Hubungan antara Social Support dan Self-Efficacy dengan Stress pada Ibu Rumah Tangga yang Berpendidikan Tinggi - Syarifah Mustika Sari; Yuliana Intan Lestari; Alma Yulianti Yulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This research aims to study about relationship between social support, self-efficacy and stress among housewives who have high education. Daily routine can lead stress on housewives. Social cognitive factors like social support and self-efficacy effect stress experience. Samples are 200 high educated housewives who don’t have a job. This research is having incidental sampling technique and using some scales for collecting data such as social support scale, self-efficacy scale, and stress scale. Data were analyzed using Multiple Regression Analysis. The results showed that there is a significant correlation between social support, self- efficacy and stress among high educated housewives with F = 2.197 and 0.00 significance (p <0.01). It means that the hypothesis proposed by the researchers that there is a correlation between social support, self-efficacy and stress are accepted.